2021
DOI: 10.4018/ijlis.20210701.oa10
|View full text |Cite
|
Sign up to set email alerts
|

Proposing a Library Consortium Model for National Development in Zimbabwe

Abstract: Globally library cooperation and collaboration is transforming the scholarship landscape as academic libraries battle to survive amidst escalating costs of subscriptions. Zimbabwe is no exception to this phenomenon as evidenced by the development of local consortia for resource sharing. The main purpose of the research is to gather the views of librarians on the need for a library consortium to support national development in Zimbabwe. The researcher used a mixed method approach. Zimbabwe does not have natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In a similar vein, Mukred (2016) also noted that adequate numbers of trained staff with the required technical skills facilitate digital records preservation. Chisita (2009) found that upgrading and equipping staff with knowledge and skills related to ICT helps organisations to deal with technological changes. It is, therefore, essential for an institution to pay enough attention to training and developing internal staff, as it enhances awareness, increases skills, knowledge, experience and commitment towards digital records preservation.…”
Section: Related Literaturementioning
confidence: 99%
“…In a similar vein, Mukred (2016) also noted that adequate numbers of trained staff with the required technical skills facilitate digital records preservation. Chisita (2009) found that upgrading and equipping staff with knowledge and skills related to ICT helps organisations to deal with technological changes. It is, therefore, essential for an institution to pay enough attention to training and developing internal staff, as it enhances awareness, increases skills, knowledge, experience and commitment towards digital records preservation.…”
Section: Related Literaturementioning
confidence: 99%